2018
DOI: 10.1186/s41938-018-0102-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bt cotton expressing single (Cry1Ac) and dual toxins (Cry1Ac and Cry2Ab) on the fitness of the predator Chrysoperla zastrowi sillemi (Esben-Petersen): prey-mediated tri-trophic analysis

Abstract: Transgenic Bt cotton with genes from soil inhabiting spore forming bacterium Bacillus thuringiensis Berliner produces δendotoxin for the control of lepidopteran insects. The prey-mediated effects of Cry protein on the third trophic level is the most realistic exposure pathway that needs to be addressed as an important component of environment risk assessment. The green lacewing, Chrysoperla zastrowi sillemi (Esben-Petersen) (Neuroptera: Chrysopidae) is the most important generalist predator in the cotton ecosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Moreover, similar trends were observed in the developmental parameters of C. z. sillemi when fed with prey reared on Bt and non-Bt cotton cultivars, indicating that the source of the prey did not signi cantly in uence developmental outcomes for the predator. In conformity with the results, several workers have also reported no adverse effect of Cry proteins on the various developmental and reproductive parameters of C. carnea, C. externa, and Geocoris pallidipennis in cotton through feeding of Bt cotton-fed A. gossypii and for wolf spiders in rice(Anitha 2015;Shera et al 2018;Niu et al 2017;Zhang et al 2022). Simon et al (2006), concluded that due to the lepidopteran-speci c nature of Cry…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Moreover, similar trends were observed in the developmental parameters of C. z. sillemi when fed with prey reared on Bt and non-Bt cotton cultivars, indicating that the source of the prey did not signi cantly in uence developmental outcomes for the predator. In conformity with the results, several workers have also reported no adverse effect of Cry proteins on the various developmental and reproductive parameters of C. carnea, C. externa, and Geocoris pallidipennis in cotton through feeding of Bt cotton-fed A. gossypii and for wolf spiders in rice(Anitha 2015;Shera et al 2018;Niu et al 2017;Zhang et al 2022). Simon et al (2006), concluded that due to the lepidopteran-speci c nature of Cry…”
supporting
confidence: 80%
“…Despite the critical role of predators like Chrysoperla spp. in pest regulation, tri-trophic interaction studies on their interaction with Bt toxins, particularly Cry2Ab, under direct rearing of aphids or white ies on Bt cotton and then feeding of these preys by predators remain limited in the Indian context (Dhillon and Sharma 2009; Magar and Budhvat 2014; Anitha 2015; Shera et al 2018). Therefore, this study aims to address this research gap by investigating tri-trophic interactions and assessing the impact of dual BG II cotton expressing Cry1Ac and Cry2Ab proteins on the development of C. z. sillemi.…”
Section: Introductionmentioning
confidence: 99%
“…The grubs of C. zastrowi sillemi are an e cient predator of B. tabaci (Naranjo and Ellsworth, 2005; and their predatory potential does not get affected when they predate on B. tabaci fed on Bt cotton. Because they are generalist predators of phloem feeders which acquire no detectable Cry proteins despite being expressed in high levels in the Bt cotton (Shera et al, 2018). Since, the type of crop does not affect the density of C. zastrowi sillemi, therefore, we observed a higher density of predatory grubs in Bt cotton, this might be due to the difference in pest density and crop phenology of Bt and non-Bt cotton.…”
Section: Discussionmentioning
confidence: 66%
“…However, there are also some studies that differed from these findings and hinted that Bt proteins had none of the apparent adverse effects on the survival of green lace wing larvae (Wang et al 2012) or other NTAs when administered through direct incorporation into the synthetic diet or indirectly through prey (Tian et al 2018). Shera et al (2018) studied the effects of single toxin (Cry 1Ac) and dual toxin (Cry1Ac and Cry 2Ab) on the fitness parameters of Chrysoperla zastrowi, sillemi (Esben-Peterson), a generalist predator in the cotton ecosystem, through its herbivore preys such as mealy bug, whitefly and leaf hoppers and concluded that both proteins were proved apparently safe on test species. The results of present experiment are similar to the above studies; however, mild delay was noted in larval developmental time, while all other life parameters remained unchanged indicating no prominent side effect of Vip3Aa on P. japonica.…”
Section: Discussionmentioning
confidence: 99%